PCR‐based prevalence of a fatal reovirus of the blue crab, Callinectes sapidus (Rathbun) along the northern Atlantic coast of the USA. Issue 6 (6th August 2015) - Flowers, E M; Simmonds, K; Messick, G A; Sullivan, L; Schott, E J
Abstract: There is a need for more information on the relationship between diseases and fluctuations of wild populations of marine animals. In the case of Callinectes sapidus reovirus 1 (CsRV1, also known as RLV), there is a lack of baseline information on range, prevalence and outbreaks, from which to develop an understanding of population‐level impacts. An RT‐qPCR assay was developed that is capable of detecting 10 copies of the CsRV1 genome. In collaboration with state, federal and academic partners, blue crabs were collected from sites throughout the north‐eastern United States to assess the northern range of this pathogen. In addition, archived crab samples from the Chesapeake Bay were assessed for CsRV1 by RT‐qPCR and histology. PCR‐based assessments indicate that CsRV1 was present at all but one site. Prevalence of CsRV1 as assessed by RT‐qPCR was highly variable between locations, and CsRV1 prevalence varied between years at a given location. Mean CsRV1 prevalence as assessed by RT‐qPCR was >15% each year, and peak prevalence was 79%. The wide geographic range and highly variable prevalence of CsRV1 indicate that more study is needed to understand CsRV1 dynamics and the role the virus plays in blue crab natural mortality.